Acute and sub-acute toxicity profile of thymoquinone-loaded nanostructured lipid carrier (TQNLC) in BALB/c mice - Yong, Sze Ong; Saiful Yazan, Latifah; Wei, Keat Ng; Noordin, Mustapha M.; Sapuan, Sarah; Jhi, Biau Foo; Yin, Sim Tor (Dove Medical Press, 2016)
Background: Thymoquinone (TQ), the predominant active lipophilic component in Nigella sativa seed oil, has a variety of pharmacological properties such as anticancer activities. However, translation of TQ to clinical phase is still not possible due to its hydrophobic properties. This problem can be solved by encapsulating it in nanoformulations to enhance its pharmacological properties. In our previous study, TQ has been successfully encapsulated in a nanostructured lipid carrier (hereinafter referred to as TQNLC) with excellent physiochemical properties such as high encapsulation efficiency, high drug-loading capacity, particle diameter less than 100nm, and stability up to 2 years. In vitro studies also proved that TQNLC exhibited antiproliferative activity toward breast and cervical cancer cell lines. However, no toxicity profile related to this formulation has been reported. In this study, we determine and compare the in vivo toxicity of both TQNLC and TQ. Materials and methods: The in vivo toxicity (acute and subacute toxicity) study was carried out by oral administration of TQNLC and TQ to BALB/c mice. Animal survival, body weight, organ weight-to-body weight ratio, hematological profile, biochemistry profile, and histopathological changes were analyzed. Results: In acute toxicity, TQ that is loaded in nanostructured lipid carrier (NLC) was found to be less toxic than pure TQ. It can be concluded that encapsulation of TQ in lipid carrier minimizes the toxicity of the compound. In the subacute toxicity study, oral administration of 100 mg/kg of TQNLC and TQ did not cause mortality to either male or female but resulted in toxicity to the liver. It is postulated that long-term consumption of TQNLC and TQ may cause toxicity to the liver but not to the extent of altering the functions of the organ. For both treatments, the no observed adverse effect level (NOAEL) was found to be 10 mg/kg/d for mice in both sexes. Conclusion: For long-term oral consumption, TQ and TQNLC at a dose of 10 mg/kg is safe in mice and does not exert any toxic effect. The results provide safety information of TQNLC, which would further help researchers in clinical use.